A formação do tradutor-intérprete de língua brasileira de sinais como intelectual específico : o trabalho de interpretação como prática de cuidado de si - Santos, Joaquim Cesar Cunha dos (2016)
Brazilian Sign Language interpreters are professionals who have become necessary in the twenty-first century, critical to the effectiveness of the inclusion of the hearing impaired. Its performance becomes therefore imperative, gaining strength so that together with new knowledge constituted in different perspectives and disciplines about Sign Language, there has emerged theoretical knowledge about these professionals, having guaranteed a professional status. Following that line of discussion, this research discusses how TILS (Sign Language Translators and Interpreters), through the rites of passage and aliturgies that guarantee the professional status of this function, subjectifies them starting from the entry into this field as professionals. Therefore, the central question of this research stands out as follows: When does the subject subjectify himself as a translator-interpreter of sign language as a specific intellectual through aliturgical rituals? To answer this question, we used the narrative research in which statements serve as the basis for understanding the processes of being and of coming to be the subject of this study. This study makes a necessary reflection on the role of the interpreter at the moment, directing the observation of these professionals, being used as the basis for these notes about the notion of the specific intellectual, a theoretical and methodological tool of Foucault's inspiration. It analyzes the narratives using Tecnologias do Eu (Technologies of Me, LARROSA, 1994), the mechanisms which produce or mediate the experience itself. By means of it, the optical mechanism determines and constitutes what is visible within the subject himself. The establishing discursive mechanism constitutes that which the subject can and should say about himself. The moral legal mechanism, where the subject is judged based on the standards and values of which it is established or not. The mechanism of the experiment itself, according to the construction itself over time. Finally, the practical mechanism that establishes what the subject can and should do with himself. Given that the practice of self-care is essential in the work of this professional, it argues how he contributes as a specific intellectual, to the end of producing the conditions of possibilities of practices involved in the interpretation work in the education of the hearing impaired.